Hello, universe eaudiobook - Kelly, Erin Entrada (2017)
Winner of the Newbery Medal "A charming, intriguingly plotted novel." —Washington Post Acclaimed and award-winning author Erin Entrada Kelly's Hello, Universe is a funny and poignant neighborhood story about unexpected friendships. Told from four intertwining points of view—two boys and two girls—the novel celebrates bravery, being different, and finding your inner bayani (hero). "Readers will be instantly engrossed in this relatable neighborhood adventure and its eclectic cast of misfits."—Booklist In one day, four lives weave together in unexpected ways. Virgil Salinas is shy and kindhearted and feels out of place in his crazy-about-sports family. Valencia Somerset, who is deaf, is smart, brave, and secretly lonely, and she loves everything about nature. Kaori Tanaka is a self-proclaimed psychic, whose little sister, Gen, is always following her around. And Chet Bullens wishes the weird kids would just stop being so different so he can concentrate on basketball. They aren't friends, at least not until Chet pulls a prank that traps Virgil and his pet guinea pig at the bottom of a well. This disaster leads Kaori, Gen, and Valencia on an epic quest to find missing Virgil. Through luck, smarts, bravery, and a little help from the universe, a rescue is performed, a bully is put in his place, and friendship blooms. The acclaimed author of Blackbird Fly and The Land of Forgotten Girls writes with an authentic, humorous, and irresistible tween voice that will appeal to fans of Thanhha Lai and Rita Williams-Garcia. "Readers across the board will flock to this book that has something for nearly everyone—humor, bullying, self-acceptance, cross-generational relationships, and a smartly fateful ending."—School Library Journal